Pengaruh Belanja Modal, Belanja Barang dan Jasa, Belanja Hibah dan Belanja Bantuan Sosial Terhadap Indeks Pembangunan Manusia di Indonesia Tahun 2010-2020 - Annissa Septiani (Syntax Idea, 2022)
This study aims to determine the effect of capital expenditures, goods and services expenditures, grant expenditures and social assistance expenditures on the human development index in Indonesia in 2010-2020. This study uses a quantitative approach. The data used in this study are secondary data from 23 provinces in Indonesia in 2010-2020. The analysis model used is multiple regression analysis with random effects model. The results of this study indicate that the capital expenditure variable has a positive and significant effect on the human development index, the variable for goods and services expenditure has a positive and significant effect on the human development index, the grant expenditure variable has a positive and significant effect on the human development index, social assistance expenditure has no negative and insignificant effect on the human development, capital expenditure, goods and services expenditure, grant expenditure and social assistance expenditure have a significant effect on the human development index.